Examining the Factors Impacting Undergraduate Satisfaction and Repurchase Intention Toward E-Commerce Platforms in Yibin, China - Li, Zhirong (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examined key factors impacting undergraduate students' satisfaction and repurchase intention toward e-commerce platforms in Yibin, China. The conceptual framework explored the relationships among System Quality (STQ), Information Quality (IQ), Service Quality (SVQ), Popularity (POP), Satisfaction (SAT), E-Trust (ET), and Repurchase Intention (RPI). Research design, data and methodology: The researcher employed a quantitative approach (n=500), administering questionnaires to undergraduate students from the School of Mechanical Engineering, Sichuan University of Science & Engineering, Yibin, China. Non-probability sampling methods included judgmental sampling for target selection, quota sampling for sample size determination, and convenience sampling for online data collection. Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) assessed model fit, reliability, and construct validity. Results: The results revealed that system quality, information quality, service quality, and popularity significantly influenced satisfaction, which acted as a mediating variable affecting repurchase intention. Information quality had the strongest impact on satisfaction, followed by service quality, system quality, and popularity. Additionally, e-trust significantly influenced repurchase intention. Conclusions: Based on these findings, e-commerce platform operators should focus on enhancing system performance, information reliability, service excellence, and platform recognition to elevate user satisfaction. Additionally, building e-trust can significantly reinforce undergraduate users' repurchase intentions.